Leprosy—Presenting as Rheumatoid Arthritis Misleading the Correct Diagnosis - Dhakal Sagar; Shrestha Kipa; Gurung Praful; Thapa Durga (Clinical Case Reports)
ABSTRACT Leprosy can present with symptoms resembling rheumatoid arthritis, leading to delays in diagnosis or inappropriate treatment, potentially progressing to lepromatous forms, neuropathy, and disability. Physicians must consider leprosy as a differential for rheumatoid arthritis, especially in endemic regions. Early detection is vital to prevent chronic neuropathy, disabilities, and disfigurement.